Table of Content - - (Journal of agricultural, environmental and veterinary sciences, 2024)
Table of Content:1. Production of asparaginase from Bacillus licheniformis using agro-industrial residues as carbon and nitrogen sourcesVivian Daifallah2. Nano particles of Silicon effects on Photochemistry components (biological activity) and physiological properties of Coriandrum sativum plant under water stressAbdullah Musfer Alghamdi, Prof. Hassan Mohammed Rashad, Dr. Mordi Mohammed Algandaby3. Exploring the Value Chains in the Small Ruminant Sector: A brief review of the literatureRula Awad, Aziza Mohamed-Brahmi, Hosam Titi, Mohamed Jaouad, Aziza Gasmi-Boubaker4. Effect of Anti-Transpirants foliar application on productivity and quality of Egyptian cotton  under water stress conditions in clay soilsDr. Amany Ahmed ELashmouny, Dr. ElSayyed Abu Al-Futouh Moursi5. Effect of different Gamma Rays doses on Seed Germination, Seedling parameter on local seed okra (Abelmoschus esculentus (L.)Wafaa Hadi Hassoon, Naeem Saeed Dheyab, Ali Jabbar Abd Alsada
Keywords: Journal of Agricultural, Environmental and Veterinary Sciences